Improving Detection of Prediabetes in Children and Adults: Using Combinations of Blood Glucose Tests - Okosun, Ike S.; Seale, J. Paul; Lyn, Rodney; Davis-Smith, Y. Monique (Frontiers in Public Health, 2015)
Aim: To determine combinations of blood glucose tests: oral glucose tolerance (OGT), fasting plasma glucose (FBG) and hemoglobin A1C (HbA1C) that are associated with highest diagnostic rates of prediabetes in non-diabetic American children and adults. Methods: The 2007-2008 U.S. National Health and Nutrition Examination Surveys data were used for this study. Overall and specific prevalence of prediabetes (defined using OGT+FPG, OGT+HbA1C, HbA1C+FPG and OGT+FPG+HbA1C tests) were determined across age, race/ethnicity, sex and BMI categories. Results: FPG+HbA1C test was associated with significantly higher diagnostic rates of prediabetes across age, race/ethnicity and BMI. Estimates of overall prevalence of prediabetes using OGT+FPG, OGT+HbA1C, HbA1C+FPG and OGT+FPG+HbA1C tests were 20.3%, 24.2%, 33% and 34.3%, respectively. Compared to OGT+FPG, the use of HbA1C+FPG test in screening was associated with 44.8%, 135%, 38.6% and 35.9% increased prevalence of prediabetes in non-Hispanic White, non-Hispanic Black, Mexican-American and other racial/ethnic men, respectively. The corresponding values in women were 67.8%, 140%, 37.2% and 42.6%, respectively. Combined use of all blood glucose tests did not improve the overall and gender-specific prediabetes prevalence beyond what was observed using HbA1C+FPG test. Conclusions: HbA1C criteria were associated with higher diagnosis rates of prediabetes than FPG and OGT tests in non-diabetic American children and adults. Using a combination of HbA1C and FPG test in screening for prediabetes reduces intrinsic systematic bias in using just HbA1C testing and offers the benefits of each test. A well-defined HbA1C that takes into consideration race/ethnicity, gender, age and body mass index may improve detection of prediabetes in population and clinical settings.